Kiveys ruuduissa 4987-4988/980-981 tasossa 3. Etelästä. - Rohiola, Ville
fyysinen kuvaus: vaaka
Keywords: kaivausdokumentointi; rautakausi; ruumiskalmistot; ruumishaudat; ristiretkiaika; Suomi, Salo, Halikon Kirkkomäki, Salo, Halikon Kirkkomäki; Halikon Kirkkomäki